Austronea phyllopogon (Hyacinthaceae, Urgineoideae), a new species from the Kamiesberg, Northern Cape Province in South Africa - Martínez-Azorín, Mario; Pinter, Michael; Crespo, Manuel B.; Alonso-Vargas, María Ángeles (Phytotaxa, 2020)
Among the recently described genera in Hyacinthaceae subfamily Urgineoideae (= Asparagaceae subfam. Scilloideae tribe Urgineeae), Austronea Mart.-Azorín, M.B.Crespo, M.Pinter & Wetschnig in Martínez-Azorín et al. (2018: 105) includes 20 species restricted to southern Africa (Martínez-Azorín et al. 2018, 2019a, 2019b). Some such species were traditionally included in Urginea Steinheil (1834: 321) or Drimia Jacq. ex Willdenow (1799: 165) sensu lato and resemble those of Fusifilum Rafinesque (1837: 27), a phylogenetic relationship supported by molecular data (Martínez-Azorín et al. in prep.). However, species of Austronea are easily identified by a unique syndrome of morphological characters, the most characteristic being the subcorymbose or congested raceme that commonly nods during early developmental stages, the green to yellowish ovary (in contrast to the white gynoecium of Fusifilum) and the tetrahedrally folded seeds with narrowly winged angles (see Martínez-Azorín et al. 2018).